(untitled) (Journal of Applied Learning and Teaching, 2023)
Designing a curriculum or teaching about the environment is another approach that helps solve environmental problems. Providing knowledge to the citizens of a country is the utmost goal in educational studies. Tourism is the fastest-growing industry in the world, creating serious environmental problems for our planet. It has been almost two decades since the concept of sustainable tourism was introduced to create awareness of tourism impacts, educate about ecological conservation, and change tourists’ behaviour to become more responsible while enjoying tourism activities in the destinations (Global Sustainable Tourism Council, 2023). This study aims to examine the concept of environmental studies or ecopedagogy and how the Sapphaya community implements this concept in practice. Six steps were identified as effective learning experiences of ecopedagogy within the local community to develop sustainable tourism in Sapphaya. A qualitative approach was adopted from Participatory Action Research with three stages of the investigation. It included the initial stage of developing ideas and engagement over a three-month period, followed by stage two of skill development over the same period, and finally, the last phase over an eight-month period of continual assessment, which was the longest stage of knowledge generation and reflection via participation.